A Case of Cementless Impaction Bone Graft in a Revision Total Hip Arthroplasty Requiring Calcar Reconstruction - Shigeo Ishiguro; Kunihiro Asanuma; Tatsuya Tamaki; Kazuhiro Oinuma; Akihiro Sudo (Case Reports in Orthopedics)
Introduction. In cases of bone deficiency or osteoporosis, and especially in revision cases, there were only two options for treatment until the impaction bone graft procedure was proposed. These were cemented or cementless femoral prosthesis. In the early 1990s, the use of impaction bone graft with a cemented mantle had gained popularity and had proven to be clinically effective. In Germany, a cementless impaction bone graft procedure using Corail® (DePuy Synthes) stems was devised, and functional scores were similar to conventional cemented Impaction bone grafts. Case presentation. A 48-year-old man presented with femur loosening of a reamed bipolar arthroplasty performed in 1990. The patient was treated with a cementless impaction bone graft using a Corail® (DePuy Synthes) stem in the femur in revision THA surgery, and the calcar was reconstructed by allograft. Results. At five years, the calcar allograft united with the host bone, and the femoral component showed no subsidence. Conclusion. Calcar reconstruction with a strut allograft, aimed at preventing sinking of the stem was key in this operation. Surgical indication for femoral cementless impaction bone graft should be for loosened femoral prosthesis in a type II Paprosky classification, where only the cortical bone of the isthmus is partially affected, cortical thinning does not exist, and it is mechanically strong enough for the allograft tip impaction. The procedure was safely feasible through the direct anterior approach.